Efficacy of Ultrasound-Guided Injections of Type I Collagen-Based Medical Device for Greater Trochanteric Pain Syndrome: A Pilot Study - Filippo Randelli; Alberto Fioruzzi; Manuel Giovanni Mazzoleni; Alessandra Radaelli; Leila Rahali; Lucia Verga; Alessandra Menon (Life)
Background: Greater Trochanteric Pain Syndrome (GTPS) is a frequent clinical condition characterized by acute or chronic pain in the lateral region of the hip. This condition is primarily due to gluteus minimus and medius tendinopathy. Swine-derived type I collagen has shown a positive effect on tenocytes through in vitro studies and on tendinopathies in clinical studies. This pilot study aims to evaluate the clinical effects of swine-derived type I collagen injections on pain, hip function, and strength in GTPS patients. Methods: The study group was treated with three ultrasound-guided swine-derived type I collagen injections once a week for three consecutive weeks. The primary endpoint was pain reduction of at least 3 points on the Numeric Rating Scale (NRS) at ten weeks. Secondary endpoints were NRS average reduction at rest and palpation, modified Harris Hip Score (mHHS), abductor strength, and magnetic resonance imaging (MRI) improvement at six months. Results: 52 patients were screened, 47 enrolled, and 43 completed the study. The primary endpoint was reached by 60.5% of the patients. All secondary endpoints were also reached with statistical significance. Neither early nor late adverse effects were found. Conclusions: In this pilot study, ultrasound-guided peritrochanteric swine-derived type I collagen injections are safe and effective for most patients with GTPS included in the study. Further and more extensive confirmatory investigation studies with a longer follow-up are needed to confirm this pilot study’s results and the clinical benefit’s persistence.